Dysregulated mTORC1-Dependent Translational Control: From Brain Disorders to Psychoactive Drugs - Santini, Emanuela; Klann, Eric (Frontiers in Behavioral Neuroscience, 2011)
In the last decade, a plethora of studies utilizing pharmacological, biochemical, and genetic approaches have shown that precise translational control is required for long-lasting synaptic plasticity and the formation of long-term memory. Moreover, more recent studies indicate that alterations in translational control are a common pathophysiological feature of human neurological disorders, including developmental disorders, neuropsychiatric disorders, and neurodegenerative diseases. Finally, translational control mechanisms are susceptible to modification by psychoactive drugs. Taken together, these findings point to a central role for translational control in the regulation of synaptic function and behavior.